The analysis of the imagery expression devices in the Lithuanian language - Piaseckienė, Karolina; Radavičius, Marijus (Lietuvos matematikos rinkinys, 2011)
Lithuanian language is characterized by imagery, which can be conveyed in a variety of expression means. One of them is metalanguage comments. In this article, metalanguage comments that describe the (emotional) tone of saying are analyzed statistically using corpus of contemporary Lithuanian language. A fitted logistic regression model describes effects which influence the proportion of the metalanguage comments among all occurrences of their basic word in a text.